Evaluation of Therapeutic Efficacy of Surgical Intervention in Dorsal Spinal Tuberculosis: Therapeutic Efficacy of Surgical Intervention in Dorsal Spinal Tuberculosis - Muzaffer uddin , Muhammad; Munwar Ali, Muhammad; Ali Jamali, Muhammad; Zulfiqar, Farrukh; Kumar, Ramesh; Muhammad Zeeshan, Qazi (Pakistan Journal of Health Sciences, 2022)
Tuberculosis (TB) is an infectious disease. The mycobacterium tuberculosis is the causative agent of TB. The prevalence of TB is influenced by the economic, sanitary, and medical conditions of the area. Although TB has the worldwide prevalence but it is most common in underdeveloped and developing nations like Pakistan, China, and several African nation. The every 24 to 32 people out of 100,000 in developed countries are suffering from TB. Objective: To analyze the surgical intervention for active dorsal spinal tuberculosis at early stage in patients suffering from paraparesis and paraplegia. Methods: This retrospective study was conducted at the neurosurgery department of the tertiary care hospital for the duration of four years and six months from January 2017 to June 2021. The study was carried out on 138 patients. There were 85 male and 53 female candidates. Written consent was taken from the patients. In order to determine the therapeutic effects of surgery, the neurological status on ASIA grading and NASCIS scores were examined. Results: Majority of the patients healed after single posterior procedure. The average time of surgery was 193 minutes approximately, and the mean blood loss was found to be 874 ml. The average motor improvement in NASCIS score for paraplegia was 78±13.1 and for paraparesis; it was 100 ± 0.0. Conclusions: In this study, it was concluded that early surgical intervention can prove to be beneficial in case of active dorsal spinal TB patients with cord compression.